ANSWER
B. For any term (x^a)(y^b) in the expansion, a + b = n
Step-by-step explanation
The Binomial Theorem formula is,
![(a+b)^n=\sum_(k=0)^n\binom{n}{k}a^(n-k)b^k](https://img.qammunity.org/2023/formulas/mathematics/college/t95l1n2bpqwlu1uuxhjfqpszm0ubtwkroh.png)
As we can see in this expression, the exponents of each term of the binomial are (n-k) and k, so, if we add them we have,
![n-k+k=n](https://img.qammunity.org/2023/formulas/mathematics/college/ykme41t8nygjec0izqbftuu7woco3tun1t.png)
This means that the sum of the exponents is always n.
On the other hand, when k = 0, the exponents are n and 0, and the coefficient of that term is,
![\binom{n}{0}=(n!)/(0!(n-0)!)=(n!)/(n!)=1](https://img.qammunity.org/2023/formulas/mathematics/college/r3m28c8zr1v6hdp88tjk99pxss3d4cjy15.png)
And, when k = n, the exponents are 0 and n, and the coefficient of that term is,
![\binom{n}{n}=(n!)/(n!(n-n)!)=(n!)/(n!0!)=(n!)/(n!)=1](https://img.qammunity.org/2023/formulas/mathematics/college/6y5bia7kck024vo4fhqq2s7wa8ehltt3pb.png)
This means that for the first and last term (when the exponents for each variable are n) the coefficients are both 1.
Hence, the two true statements are B and C.